Proteome-wide dataset generated by iTRAQ-3DLCMS/MS technique for studying the role of FerB protein in oxidative stress in Paracoccus denitrificans - Pernikářová, Vendula; Sedláček, Vojtěch; Potěšil, David; Procházková, Iva; Zdráhal, Zbyněk; Bouchal, Pavel; Kučera, Igor (Data in brief, 2015)
3DLC protein- and peptide-fractionation technique combined with iTRAQ-peptide labeling and Orbitrap mass spectrometry was employed to quantitate Paracoccus dentirificans total proteome with maximal coverage. This resulted in identification of 24,948 peptides representing 2627 proteins (FDR<0.01) in P. dentirificans wild type and ferB mutant strains grown in the presence or absence of methyl viologen as an oxidative stressor. The data were generated for assessment of FerB protein role in oxidative stress as published by Pernikářová et al.; proteomic responses to a methyl viologen-induced oxidative stress in the wild type and FerB mutant strains of P. denitrificans, J. Proteomics 2015;125:68-75. Dataset is supplied in the article.